Transient Expression of Tetrameric Recombinant Human Butyrylcholinesterase in Nicotiana benthamiana - Alkanaimsh, Salem; Karuppanan, Kalimuthu; Guerrero, Andrés; Tu, Aye M.; Hashimoto, Bryce; Hwang, Min Sook; Phu, My L.; Arzola, Lucas; Lebrilla, Carlito B.; Dandekar, Abhaya M.; Falk, Bryce W.; Nandi, Somen; et al. (Frontiers in Plant Science, 2016)
To optimize the expression, extraction and purification of plant-derived tetrameric recombinant human butyrylcholinesterase (prBChE), we describe the development and use of plant viral amplicon-based gene expression system; Tobacco Mosaic Virus RNA-based overexpression vector (TRBO) to express enzymatically active FLAG-tagged plant made recombinant butyrylcholinesterase in Nicotiana benthamiana leaves using transient agroinfiltration. Two gene expression cassettes were designed to express the recombinant protein in either the endoplasmic reticulum or to the apoplastic compartment. Leaf homogenization was used to isolate endoplasmic reticulum-retained recombinant butyrylcholinesterase (prBChE-ER) while apoplast-targeted recombinant butyrylcholinesterase was isolated by either leaf homogenization (prBChE) or vacuum-extraction of apoplastic wash fluid (prBChE-AWF). Recombinant butyrylcholinesterase from apoplast wash fluid had a higher specific activity but lower enzyme yield than leaf homogenate. To optimize the isolation and purification of total recombinant protein from leaf homogenates, an acidic extraction buffer was used. The acidic extraction buffer yielded >95% enzymatically active tetrameric recombinant butyrylcholinesterase as verified by Coomassie stained and native gel electrophoresis. Furthermore, when compared to human butyrylcholinesterase, the prBChE was found to be similar in terms of tetramerization and enzyme kinetics. The N-linked glycan profile of purified prBChE-ER was found to be mostly high mannose structures while the N-linked glycans on prBChE-AWF were primarily complex. The glycan profile of the prBChE leaf homogenates showed a mixture of high mannose, complex and paucimannose type N-glycans. These findings demonstrate the ability of plants to produce recombinant butyrylcholinesterase that is enzymatically active and whose oligomeric state is comparable to mammalian butyrylcholinesterase. The process of plant made recombinant butyrylcholinesterase tetramerization and strategies for improving its pharmacokinetics properties are also discussed.